Work and Leisure in America - Giuseppe Ruggeri (FriesenPress, 2022)
This book describes the social, political and economic developments in the U.S. from 1950 to 2019 and provides insights into potential future trends.
Keywords: J10; 330; work and leisure; America; institutions; economic growth